Real-time driving monitoring system on a single-board computer utilizing deep neural networks integrated with MiDAS - Kaisar, Sazeed; Jim, Reduan Masud; Islam, Rian (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.